Influence of Enviromental, Social, and Governance (ESG) and Company Size on Company Value in Basic Materials Sector (2021-2023) - Febrianti, Dela; Munari, Munari (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: The study aims to examine the influence of Enviromental, Social, and Governance (ESG) and company size on company value. Methodology: The methodology describes the quantitative approach, purposive sampling, and use of secondary data from the annual reports and sustainability reports of 31 companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. Multiple linear regression analysis was applied.. Results: The results show that ESG does not contribute to company value, while company size has a significant impact. Fidings: The findings highlight the absence of a significant impact of ESG on company value, contrary to the common belief that ESG drives company value. However, company size was found to have a significant impact on company value. Novelty: The uniqueness of this study lies in its exploration of ESG in the basic materials sector, providing new insights into how non-financial factors, such as ESG, affect company value in emerging markets such as Indonesia. Originality: Originality is demonstrated by combining ESG and company size into a single model to assess their impact on company value, particularly in the context of companies listed on the Indonesia Stock Exchange (IDX). Conclusion: The conclusion emphasizes that although ESG does not significantly affect company value, company size plays a key role in determining company value. Type of Paper: This article is accurately classified as a research article, focusing on empirical data analysis.